Efeito de dois probióticos, Saccharomyces boulardii e Saccharomyces cerevisiae linhagem UFMG 905, na resposta inflamatória induzida por Salmonella enterica subsp. enterica sorovar. Typhimurium - Flaviano dos Santos Martins (2008)
Probiotics are defined as viable microorganisms that exhibit a beneficial effect on the host health when ingested in adequate amounts. Many species of bacteria are used for this purpose and the only one yeast used as probiotic in humans is Saccharomyces boulardii. Previous results in our laboratory showed that Saccharomyces cerevisiae strain UFMG 905, isolated from “cachaça” production, was able to colonize and survive in the gastrointestinal tract of germ-free and conventional mice, respectively, and to protect these animals against oral challenge with Salmonella enterica subsp. enterica serovar Typhimurium and Clostridium difficile. In the first part of this work, the effects of S. cerevisiae UFMG 905 on the translocation of Salm. Typhimurium to mesenteric lymph nodes, Peyer’s patches, spleen and liver, as well as on the immune system by number of Küpffer cells, immunoglobulin production and clearance of Escherichia coli B41, were evaluated in gnotobiotic and/or conventional mice. The treatment with the yeast reduced significantly the translocation of Salm. Typhimurium to liver in gnotobiotic animals and to all the organs tested in conventional mice. The number of Küpffer cells per 100 hepatocytes in liver was significantly higher (P < 0.05) in yeast mono-associated mice (52.9 ± 15.7) than in germ-free controls (38.1 ± 9.0). Probably, as a consequence, clearance of E. coli B41 from the bloodstream was more efficient in yeast mono-associated animals when compared to germ-free mice. Higher levels (P < 0.05) of sIgA in intestinal content and of IgA and IgM in serum were observed in yeast mono-associated mice when compared to germ-free group. Concluding, the protection against pathogenic bacteria observed in a previous study was probably due to a modulation of both local and systemic immunity of mice treated with S. cerevisiae UFMG 905. In a second part of this work, we have studied the effects of S. boulardii and S. cerevisiae UFMG 905 on the inflammation and signal transduction induced by Salm. Typhimurium ATCC 14028 in T84 cells. We have observed that both probiotics maintained the transmonolayer electrical resistance and significantly diminished IL-8 secretion in Salm. Typhimurium 14028-infected T84 cells (P < 0.05). Saccharomyces cerevisiae UFMG 905 and S. boulardii also decreased significantly the levels of Salm. Typhimurium 14028 invasion (P < 0.05), but had no effect on Salm. Typhimurium 14028 growth or adhesion to T84 cells. Differently from S. boulardii, S. cerevisiae UFMG 905 was not implicated in the diminution of the activation of Rac1 and Cdc42 in Salm. Typhimurium 14028-infected cells, which are Rho-GTPases activated by the bacteria involved in the internalization of invasive bacteria. The binding of Salm.Typhimurium 14028 to S. cerevisiae UFMG 905 and S. boulardii surface instead of T84 cells may be responsible for the diminution of invasion and activation of MAPKs (mitogen-activated protein kinases) and consequently by the diminution of IL-8 levels, since this process diminishes the number of bacteria bound to T84 cells. However, the diminution of IL-8 may also be explained by an immunomodulation through secretion of anti-inflammatory cytokines, such as IL-10, but this hypothesis was not tested in this work. The presence of the yeasts in Salm. Typhimurium 14028-infected cells also reduced and/or inhibited the phosphorylation of ERK1/2, p38 and JNK MAPKs, but did not inhibit NF-κB DNA binding activity, suggesting that the diminution of IL-8 levels was not due to inhibition of the IL-8 transcription factor but more probably to the effects of the yeasts on the p38 MAPK inhibition, which is responsible for the stabilization of IL-8 mRNA. The inhibition of JNK by the yeasts may be another explanation, once AP-1, another IL-8 transcription factor, is dependent on the phosphorylation of this protein. Finally, S. cerevisiae UFMG 905 and S. boulardii inhibited the activation of anti-inflammatory mechanism (PI3K/Akt pathway) induced by Salm. Typhimurium 14028 in T84 cells. Concluding, S. cerevisiae UFMG 905 and S. boulardii showed a protective and modulating effect on barrier function and signal transduction pathway in T84 cells when infected by Salm. Typhimurium 14028.